TRAINING COURSE AS AN ORGANIZATIONAL FORM OF STUDENTS' TEACHING INTERNSHIP - T. A. Isaeva; O. F. Shikhova (Russian State Vocational Pedagogical University, 2015)
The research objective is to analyze the introduction of interactive educational technologies and methods during the teaching internship. The authors consider that a pedagogical concept «teaching internship» as an interactive form of the educational organization for students can be a useful possibility. This form is aimed at the development of students' personal qualities for their future professional and pedagogical activities. The paper presents the types of internship training focused on the development of students' personal qualities and willingness for future vocation and teaching, such as professional teaching, research, educational-rojecting and integrated types. The methods. The teaching professional training methodology involves SWOT-analysis to help students to gain the experience in the analysis of real pedagogical situations which are relevant for a particular educational organization and for education in general. On the basis of the group expert assessment method and the pedagogical aims arrangement by B. Bloom, the authors have worked out their own specific taxonomic model for reasoned training course tasks' development; and the readiness level diagnostics of students involved in teaching internship. The results. The authors reveal new approaches to teaching internship organization for incoming vocational education teachers. It is specially noted that the training organization on the stages of teaching practice of bachelors provides not only constant feedback with the teaching internship head or tutor allowing to correct a practical activity but significantly increases students' willingness to complete it in various educational institutions as well. Scientific novelty. The authors not only introduce the concept of «pedagogical training» but also supplement it, defining its aims and objectives. It is proved that SWOT-analysis usage as the strategic planning method during teaching course provides internal and external factors identifying relevant to organization activities. Practical significance. The research findings can be used while teaching internship. The authors suggest their own new practice organization approaches for forming and determining general- cultural and professional abilities that allows preparing the student for future professional and educational activities.